2010
DOI: 10.1111/j.1469-8986.2010.01016.x
|View full text |Cite
|
Sign up to set email alerts
|

Schizotypal traits and N400 in healthy subjects

Abstract: We examined whether correlations previously found between symptoms of schizophrenia patients and the amplitude of an event-related potential (ERP), the N400, could be also found between schizotypal experiences of healthy subjects and the N400. We chose a semantic categorization task previously used with patients. Schizotypal experiences were measured with the schizotypal personality questionnaire (SPQ). The effects of the other factors were controlled for when assessing the correlations between each SPQ factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 63 publications
3
24
1
Order By: Relevance
“…() proposed that mistrust may be associated with this decreased activation of congruent associations. A number of ERP studies have reported larger N400 amplitudes in response to congruent prime–target pairings, and researchers from these studies have attributed this decrease in activation for congruent trials as being due to participants’ mistrust (e.g., Kiang & Kutas, ; Prévost et al., ). Similarly, we found that children in the friend‐made condition demonstrated larger N400 amplitudes to congruent trials compared to children in the speaker‐made condition, suggesting the possibility that children's lack of N400 in the friend‐made condition was due to their mistrust of the speaker.…”
Section: Discussionmentioning
confidence: 99%
“…() proposed that mistrust may be associated with this decreased activation of congruent associations. A number of ERP studies have reported larger N400 amplitudes in response to congruent prime–target pairings, and researchers from these studies have attributed this decrease in activation for congruent trials as being due to participants’ mistrust (e.g., Kiang & Kutas, ; Prévost et al., ). Similarly, we found that children in the friend‐made condition demonstrated larger N400 amplitudes to congruent trials compared to children in the speaker‐made condition, suggesting the possibility that children's lack of N400 in the friend‐made condition was due to their mistrust of the speaker.…”
Section: Discussionmentioning
confidence: 99%
“…Klein and colleagues (164) observed a reduction in P300b amplitude in participants with higher overall schizotypy (SPQ), complementing P300 amplitude changes that had been reported in patients with schizophrenia and their relatives (165). In another study, stronger negativity in the N400 window was found to be associated with higher scores in the SPQ disorganized dimension (166). Koychev and colleagues (167) studied a working memory task and found that participants with high SPQ schizotypy had reduced network synchronization in the beta and gamma range in fronto-central and central-occipital regions, compatible with the observation of disturbed cortico-cortical connectivity in schizophrenia.…”
Section: Genetic Cognitive and Neurobiological Studies Of Schizotypmentioning
confidence: 93%
“…For example, we have been looking at the N400 event-related brain potential 5 , a negative waveform that is elicited 400 ms after the onset of meaningful stimuli such as words as concrete words (e.g., banana) that activate both visual and verbal representations, than for abstract words (e.g., idea), which activate only verbal representations 7,8 . Research also supports the idea that even mild symptoms of schizophrenia, as measured by schizotypy scales, are associated with abnormally excessive semantic activation of the N400 9 . As such, we are exploring whether antipsychotic medication, which decreases schizophrenic symptom presentation, normalizes abnormal semantic activations of the N400 in healthy individuals with high levels of schizotypy.…”
Section: Introductionmentioning
confidence: 53%